Determinants of digital financial literacy: An exploratory study - Jamnani Ajay; Jamnani Jyoti (ITM Web of Conferences)
Digital financial literacy is an important attribute for understanding consumer behaviour and financial decisions in the digital financial domain. This study aims to explore determinants of digital financial literacy (DFL) that influence customer’s decision making. A quantitative approach was adopted to for the study and data was collected with the help of a structured questionnaire. Sample respondents of 438 who use digital financial services, were used for the study. The study also aimed at finding association between demographic details of the respondent and digital financial services been consumed. Findings revel seven factors being identified that influence consumer’s decision making namely digital responsibility, risk awareness, financial planning, digital competency, prudent finance, budgeting skills and short-term financial focus. The study also found association between age and likelihood of sharing OTP but differed for sharing usernames, passwords and PIN. financial focus